A FACILE STUDY OF THE STATUTORY CHALLENGES CONCERNING CUSTOMARY PRACTICE OF INTESTATE SUCCESSION IN NIGERIA - Paul Atagamen Aidonojie; Oaihimire Idemudia Edetalehn (JHR (Jurnal Hukum Replik), 2023)
The custom and tradition of Nigeria is an outgrowth from the history of the society. In this regard, customary law emanate from the spirit of the people. However, it has been observe that by the locally made Wills Law of some state in Nigeria, it recognize and preserve the Nigerian’s customary practice of intestate succession. However, the Wills Act of 1837 which applies to all state except state that have enact their wills law, seem to create a limitation on customary intestate succession. It is in this regard, that this study adopts a hybrid method of research in analysing the statutory preservation and limitation of Nigeria’s customary practice of intestate succession by the wills laws and Act in Nigeria. The study made use online survey questionnaires sent to 308 legal practitioners (randomly selected) in the various states of the federal republic of Nigeria. A descriptive and an analytical statistic were used to analyse 308 respondent responses to the questionnaire. The study found that 76% of the respondent identify that Wills Act places customary limitation on customary intestate succession and they prefer the Wills Laws of 1958, given it preservation of the Nigerian custom and traditions concerning intestate succession. It was therefore, concluded and recommended that there is a need for some of those states that still applies the Wills Act of 1837, to enact or amend the Wills Act to recognised customary intestate succession.